Tau Oligomers as Potential Targets for Alzheimer’s Diagnosis and Novel Drugs - Guzman-Martinez, Leonardo; Farias, Gonzalo A.; Maccioni, Ricardo B. (Frontiers in Neurology, 2013)
A cumulative number of approaches have been carried out to elucidate the pathogenesis of Alzheimer´s disease (AD). Tangle formation has been identified as a major event involved in the neurodegenerative process, due to the conversion of either soluble peptides or oligomers into insoluble filaments. Most of recent studies share in common the observation that formation of tau oligomers and the subsequent pathological filaments arrays is a critical step in AD etiopathogenesis. Oligomeric tau species appear to be neurotoxic for neuronal cells, and therefore appear as an appropriate target for the design of molecules that may control morphological and functional alterations leading to cognitive impairment. Thus, current therapeutic strategies are aimed at three major types of molecules: 1) Inhibitors of protein kinases and phosphatases that may control neuronal degeneration, 2) Methylene blue, and 3) Natural phytocomplexes and polyphenolics compounds able to either inhibit the formation of tau filaments or disaggregate them. Only a few polyphenolic molecules have emerged to prevent tau aggregation. Fulvic acid, a humic substance, has a potential activity to protect cognitive impairment. In fact, formation of paired helical filaments (PHFs) in vitro, is inhibited by fulvic acid affecting the length of fibrils and their morphology.